2016
DOI: 10.1590/1980-5373-mr-2015-0581
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Absorbing Properties of NiFe2O4 Nanosheets Synthesized Via a Simple Surfactant-Assisted Solution Route

Abstract: NiFe 2 O 4 nanosheets have been synthesized via a simple surfactant-assisted solution route, which are confirmed by X-ray powder diffraction, scanning electron microscopy and transmission electron microscopy. The NiFe 2 O 4 sample exhibits the sheet-like structure, with width varying from 200 to 800 nm and thickness ranging from 20 to 60 nm. The electromagnetic properties of NiFe 2 O 4 nanosheetsparaffin composites have been deeply investigated. The multiple dielectric relaxation loss in NiFe 2 O 4 nanosheets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The substitution of Fe 3+ by Al 3+ was also observed in another spinel system ZnFe2O4 as a study conducted by Toledo et al [25]. There are no other impurities or secondary elements detected other than the common elements within steel such as Mn, Si, Cu, Ni, Cr, Mo, Al [26].…”
Section: IIIsupporting
confidence: 56%
See 1 more Smart Citation
“…The substitution of Fe 3+ by Al 3+ was also observed in another spinel system ZnFe2O4 as a study conducted by Toledo et al [25]. There are no other impurities or secondary elements detected other than the common elements within steel such as Mn, Si, Cu, Ni, Cr, Mo, Al [26].…”
Section: IIIsupporting
confidence: 56%
“…At higher frequency, the absorption is still suspected coming from the contribution of the aluminum plate that is shifted to lower frequency. Zhao et al [26] found that the reflection loss of NiFe2O4 nanosheets are thickness dependant at 8 -12 GHz rather than from the contribution of the ferromagnetic resonance since the permeability drops drastically in the MHz range [28].…”
Section: IIImentioning
confidence: 99%
“…Furthermore, easy preparation and high corrosion resistance, saturation magnetization, superior antioxidation, magnetocrystalline anisotropy, and application-desired structural compatibility are important characteristics of nickel-based compounds that can be used in electrical and electronic applications. 27,28…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The capacitors are essentially required to be employed at the shield boundaries to prevent high-frequency current-induced spurious radiations . Nanonickel and its ferritic compounds were widely utilized in electrodes for ceramic capacitors. , Reports on the manufacture of electrodes for capacitors using ultrafine nickel powder and the manufacture of microwave absorption of nickel ferritic compound suggest that nickel powder and its compounds are not limited to this application, which can be used as an electrode material for secondary cell, fuel cell, and others such as thin-layer laminated ceramic capacitors due to their reduced electrical resistance and it prevents the delamination or cracks of thin multilayered capacitor when the capacitor is under stress. Furthermore, easy preparation and high corrosion resistance, saturation magnetization, superior antioxidation, magnetocrystalline anisotropy, and application-desired structural compatibility are important characteristics of nickel-based compounds that can be used in electrical and electronic applications. , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…These materials are the materials of magnetic ceramics such as (ferrite) which has been developing to intervene in the construction of electrical circuits working at low frequencies and high (ferrite) is generally a set of iron oxides which are solid and fragile materials such as ceramics (Kombaiah et al, 2017) With different chemical structures and crystalline structure, all of which are semi-conductive magnetic materials ferrite has a high electrical resistivity of up to 10 Ω and is accompanied by high magnetic permeability and constant isolation ranging from 10-15 as these quantities change by electric and magnetic sfields (Ismail et al, 2007). The increasing need for materials absorbs the energy of electromagnetic waves falling on them there are several applications of electromagnetic pads manufactured from the material of the material (Zhao et al, 2016), for example, avoid unwanted electromagnetic waves and generated internally in the devices and the prevention of electromagnetic noise as well as improve the performance of antennas and the construction of audio rooms and camouflage military places and aircraft and other military applications (Shtarkova and Dishovsky, 2009). The absorbent materials are classified, according to their technical and design specifications to several types, each with its uses and specials including narrow-band pipettes.…”
Section: Introductionmentioning
confidence: 99%